PENINGKATAN KEMAMPUAN BERBICARA BAHASA INGGRIS DENGAN METODE DEBAT UNTUK MAHASISWA FAKULTAS HUKUM UNIVERSITAS RIAU KEPULAUAN - Artanto, Tri; Megah, Suswanto Ismadi; Maileni, Dwi Afni (ASOSIASI IDEBAHASA KEPRI, 2024)
This activity was aimed to improve English speaking skills by using debate methods to improve English language skills for students of the Law Study Program at the University of Riau Kepulauan. Mastering English skills and improving the quality of speaking in a foreign language were able to improve English speaking performance in handling legal cases involving foreigners in the jurisdiction of the Riau Islands province. The material used in English debates was very effective in improving Law Students' English skills. The results of the training showed an improving of the students of the Faculty of law’s' speaking abilities, understanding, knowledge and grades. Apart from that, the level of students' ability to understand to improve their abilities is very high. In conclusion, Debate requires students to argue, defend opinions and conclusions which require students to think before expressing their opinions. This certainly provides an opportunity for participants who are usually less active in learning activities in class to become active because they have to convey arguments or answer questions given by other groups to improve their language skills. these students increase. Apart from that, this training also received a high level of satisfaction from participants in terms of material, instructors, teaching methods. Overall, this training succeeded in providing positive results and met the participants' expectations in their preparation to improve their speaking skills using English.